Megafaunal Ecology of the Western Clarion Clipperton Zone - Durden, Jennifer M.; Putts, Meagan; Bingo, Sarah; Leitner, Astrid B.; Drazen, Jeffrey C.; Gooday, Andrew J.; Jones, Daniel O. B.; Sweetman, Andrew K.; Washburn, Travis W.; Smith, Craig R. (Frontiers in Marine Science, 2021)
The Clarion Clipperton Zone (CCZ) is a vast area of the central Pacific Ocean where the abyssal seabed is a focus for future polymetallic nodule mining. Broad-scale environmental gradients occur east-to-west across the CCZ seabed, including organic matter supply and nodule abundance, factors that influence benthic faunal community structure and function. A network of protected areas across the CCZ, called Areas of Particular Environmental Interest (APEIs), has been designated to cover this variation. Most previous studies of the benthic environment and megafaunal communities have focussed on the eastern CCZ, leaving the impact of these large-scale gradients unexamined and the network design untested. Seamounts are a further source of heterogeneity in the region. We examined the benthic megafaunal ecology of three APEIs in the western CCZ, spanning a range of environmental conditions. We used a combination of seabed photography and direct sampling to assess the environment and megafauna on the soft sediment habitats on the abyssal plain in three APEIs, and seamounts in two of those APEIs. We found that environmental conditions on abyssal plains differed between the three APEIs in terms of water depth, nodule abundance and coverage, sediment particle size distribution, and estimated organic matter flux. Megafauna were low density and high diversity, with few common morphotypes between sites and many morphotypes being observed only once. Xenophyophores dominated the assemblages. The density and diversity of invertebrates were greater at the sites with lower organic matter inputs and greater nodule abundance. Seamounts in the same APEIs were nodule-free and had coarser sediments than on the plain. Invertebrate megafaunal diversity was lower on the seamounts than on the plains, and most morphotypes recorded on the seamounts were only found on seamounts. Low morphotype overlap also suggests little connectivity between APEIs, and between seamounts and adjacent abyssal plains. Our results provide the first evaluation of the seabed habitats and megafaunal ecology in the western CCZ, highlighting environmental gradients that influence benthic communities, and are important for evaluating the design of the network of protected areas.